Reflections on the development of the Luta Marajoara in Physical Education classes: an integrative review (Research, Society and Development, 2022)
This study aimed to discuss the development of Luta Marajoara in Physical Education classes. This work is characterized as an integrative literature review. Data collection took place from the Scielo, Lilacs and Google Scholar databases, using the descriptors: “Fight Marajoara AND Physical Education”, “Fight Marajoara AND Basic Education” and “Fight Marajoara AND School”. The results indicate that the development of this corporal practice in Physical Education classes is not very effective, because the initial training of Physical Education teachers does not present sufficient subsidies for them to be able to effectively appropriate this theme. However, the development of the BNCC introduces this practice to the school context, arousing curiosity for the understanding of this corporal practice. In this way, we can conclude that the teacher must provide methodologies that expand students' understanding of the social, cultural and motor aspects of the Marajoara Fight, facilitating students' knowledge of this corporal practice and breaking stereotypes related to the development of fights in Education classes. Physics.